Exploring the Efficacy of Multisensory Stimulation Therapy in Addressing Communication Challenges and Social Isolation in Individuals with Transcortical Aphasia: A Hybrid Methodological Approach - Iskandarsyah Siregar (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
The study aims to delve deeply into the communication challenges faced by individuals with specific language disorders caused by brain damage, such as Transcortical Aphasia. These disorders not only serve as an obstacle to these individuals' social and personal adjustment but also lead to further complications like social isolation due to mispronunciation and feelings of embarrassment. This research posits that the challenges these individuals face are not only their own but extend to those around them who wish to communicate effectively with them. Employing a hybrid methodology that integrates both qualitative and quantitative analyses, the research scrutinizes the effectiveness of Multisensory Stimulation therapy as a learning method for individuals with language disorders. The study is framed as classroom action research, designed to evaluate the real-world implications of implementing such a therapy in a learning environment. The overarching conclusion of the study suggests that Multisensory Stimulation therapy has a considerable positive impact on improving language abilities and social interactions for people with Transcortical Aphasia. However, the research also underscores the need for further refinement in the implementation strategies, tactics, and learning models based on Multisensory Stimulation therapy. It calls for the adaptation and coordination of these learning methodologies to adhere to principles of effectiveness and efficiency rigorously. By doing so, the study aims to contribute to a more nuanced understanding of language disorders and offer tangible solutions for improving the quality of life for affected individuals and their social circles.